2019
DOI: 10.1021/acs.jmedchem.9b00681
|View full text |Cite
|
Sign up to set email alerts
|

Development of Dual Chitinase Inhibitors as Potential New Treatment for Respiratory System Diseases

Abstract: Acidic mammalian chitinase (AMCase) and chitotriosidase-1 (CHIT1) are two enzymatically active proteins produced by mammals capable of cleaving the glycosidic bond in chitin. Based on the clinical findings and animal model studies, involvement of chitinases has been suggested in several respiratory system diseases including asthma, COPD, and idiopathic pulmonary fibrosis. Exploration of structure–activity relationships within the series of 1-(3-amino-1H-1,2,4-triazol-5-yl)-piperidin-4-amines, which was earlier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…Interestingly, it was shown that inhibition of CHIT1 has more favorable therapeutic effects than nintedanib and comparable therapeutic efficiency to pirfenidone in the bleomycin-induced pulmonary fibrosis model ( 24 , 67 ). CHIT1 is recently considered as a novel therapeutic target in IPF and the first-in-class CHIT1 inhibitor is currently studied as a potential treatment for IPF ( 68 , 69 ). Based on our study’s novel finding that baseline serum CHIT1 activity could discriminate stables from progressors, we believe that CHIT1 could be useful as a potential biomarker of prognosis for the clinical practice in IPF, however further studies are warranted to confirm the present study results.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it was shown that inhibition of CHIT1 has more favorable therapeutic effects than nintedanib and comparable therapeutic efficiency to pirfenidone in the bleomycin-induced pulmonary fibrosis model ( 24 , 67 ). CHIT1 is recently considered as a novel therapeutic target in IPF and the first-in-class CHIT1 inhibitor is currently studied as a potential treatment for IPF ( 68 , 69 ). Based on our study’s novel finding that baseline serum CHIT1 activity could discriminate stables from progressors, we believe that CHIT1 could be useful as a potential biomarker of prognosis for the clinical practice in IPF, however further studies are warranted to confirm the present study results.…”
Section: Discussionmentioning
confidence: 99%
“…The other active chitinase in human tissue is acidic mammalian chitinase (AMCase), which has also been implicated in the pathogenesis of bronchial asthma and other inflammatory conditions [ 89 ]; however, it has never been studied in cystinosis. The recent development of selective chitotriosidase and dual chitinase inhibitors with very good safety profiles [ 87 , 90 ] may provide further hope to address inflammatory disorders in a pathway that may not cause harm to the kidneys. It would be interesting to see the actions of such inhibitors in inflammation-associated conditions primarily affecting the kidney, such as cystinosis.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The already described argifin has an insecticide potential demonstrated in Periplaneta americana ( Omura et al, 2000 ). Furthermore, chitinase inhibitors can also be employed to relieve the symptoms of respiratory diseases, since chitinolytic activity and chitinase expression levels increases during pulmonary inflammations, aggravating it ( Létuvé et al, 2010 ; Mazur et al, 2019 ). For instance, the already described allosamidin was observed to reduce the asthma inflammatory process by reducing lymphocyte and eosinophil recruitment to mouse lungs ( Zhu et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%